1993
DOI: 10.1038/ng0993-83
|View full text |Cite
|
Sign up to set email alerts
|

Primary amenorrhoea and infertility due to a mutation in the β–subunit of follicle–stimulating hormone

Abstract: We report a woman with primary amenorrhoea and infertility associated with an isolated deficiency of pituitary follicle-stimulating hormone (FSH), but normal luteinizing hormone (LH) secretion. Ovulation was induced by administration of exogenous FSH and resulted in a successful pregnancy. Sequence analysis of the FSH beta-subunit gene indicated that she is homozygous for a two nucleotide frameshift deletion in the coding sequence. Her mother and son are heterozygous for this mutation. This deletion results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
135
0
6

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(146 citation statements)
references
References 23 publications
5
135
0
6
Order By: Relevance
“…2). One of these involves a two base-pair deletion at codon 61 of the gene, causing a frame shift, premature stop and a truncation of the FSHb protein, rendering it completely inactive (Matthews et al 1993). The second mutant, Tyr76X, also causes truncation of the protein (Layman et al 2002) and in vitro expression of the mutant causes complete abrogation of both immuno-and bio-activity.…”
Section: Fshb Mutationsmentioning
confidence: 99%
“…2). One of these involves a two base-pair deletion at codon 61 of the gene, causing a frame shift, premature stop and a truncation of the FSHb protein, rendering it completely inactive (Matthews et al 1993). The second mutant, Tyr76X, also causes truncation of the protein (Layman et al 2002) and in vitro expression of the mutant causes complete abrogation of both immuno-and bio-activity.…”
Section: Fshb Mutationsmentioning
confidence: 99%
“…A very limited number of physiopathological situations associated with a lack of FSH secretion (Mathews et al 1993) or with FSHR genetic defects (Aittomaki et al 1995, Taipanainen et al 1997 have been reported in man. The recent report of FSH subunit as well as FSH receptor gene inactivation by homologous recombination in mice can be considered as a phenocopy of a receptor inactivating mutation (Kumar et al 1997, Sairam et al 1998.…”
Section: Discussionmentioning
confidence: 99%
“…FSH-β is located at 11p13, and mutations in this gene are reported in two women primary amenorrhea [60]. FSH receptor is crucial for recruitment of ovarian follicles and follicular maturation from and beyond the preantral stage [15,25].…”
Section: Autosomal Poi Genesmentioning
confidence: 99%